2004
DOI: 10.1021/bi0491200
|View full text |Cite
|
Sign up to set email alerts
|

Sterol Carrier Protein-2-Facilitated Intermembrane Transfer of Cholesterol- and Phospholipid-Derived Hydroperoxides

Abstract: Sterol carrier protein-2 (SCP-2) facilitates cholesterol (Ch) and phospholipid (PL) transfer/exchange between membranes and appears to play a key role in intracellular lipid trafficking. Whether SCP-2 can also facilitate lipid hydroperoxide (LOOH) transfer between membranes and thereby potentially enhance dissemination of peroxidative damage was examined in this study. Transfer kinetics of photochemically generated cholesterol hydroperoxide (ChOOH) species (5alpha-OOH, 6alpha/6beta-OOH, 7alpha/7beta-OOH) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 45 publications
6
54
0
Order By: Relevance
“…This is close to the calculated mass (3676.13 Da) for a biotinylated AviTag extension proteolytically cleaved at lysine 122, the penultimate C-terminal residue of human SCP-2 [11,25]. Using Ellman's reagent for thiol determination [37], we also showed that a bSCP-2 preparation contained 0.85 ± 0.05 mol cysteine/mol protein, which agrees with evidence [14,38] that there is a single accessible cysteine residue in SCP-2. Collectively, the properties described for bSCP-2 confirmed that it was the protein we expected.…”
Section: Molecular Characteristics Of Bscp-2supporting
confidence: 83%
See 4 more Smart Citations
“…This is close to the calculated mass (3676.13 Da) for a biotinylated AviTag extension proteolytically cleaved at lysine 122, the penultimate C-terminal residue of human SCP-2 [11,25]. Using Ellman's reagent for thiol determination [37], we also showed that a bSCP-2 preparation contained 0.85 ± 0.05 mol cysteine/mol protein, which agrees with evidence [14,38] that there is a single accessible cysteine residue in SCP-2. Collectively, the properties described for bSCP-2 confirmed that it was the protein we expected.…”
Section: Molecular Characteristics Of Bscp-2supporting
confidence: 83%
“…The low level of CHAPS (0.001%, w/v) used in running buffers also proved important for minimizing lipid losses on plastic tubing and other surfaces. In addition, EDTA and DFO were included to prevent any copper-or iron-catalyzed oxidation of bSCP-2 or lipid analytes [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations